Statistical models suggest presence of two distinct subpopulations of miniature EPSCs in fast-spiking interneurons of rat prefrontal cortex. (20th August 2015) - Malkin, S.L.; Kim, K.K.; Tikhonov, D.B.; Magazanik, L.G.; Zaitsev, A.V.
Graphical abstract: Highlights: Miniature EPSCs were recorded in fast-spiking interneurons (FSIs) and pyramidal cells. The shapes of mEPSC amplitude distributions differ in the FSIs and pyramidal cells. Statistical models suggest the presence of two distinct populations of mEPSCs in FSIs. Abstract: Properties of excitatory synaptic responses in fast-spiking interneurons (FSIs) and pyramidal neurons (PNs) are different; however, the mechanisms and determinants of this diversity have not been fully investigated. In the present study, voltage-clamp recording of miniature excitatory post-synaptic currents (mEPSCs) was performed of layer 2–3 FSIs and PNs in the medial prefrontal cortex of rats aged 19–22 days. The average mEPSCs in the FSIs exhibited amplitudes that were two times larger than those of the PNs and with much faster rise and decay. The mEPSC amplitude distributions in both cell types were asymmetric and in FSIs, the distributions were more skewed and had two-times larger coefficients of variation than in the PNs. In PNs but not in FSIs, the amplitude distributions were fitted well by different skewed unimodal functions that have been used previously for this purpose. In the FSIs, the distributions were well approximated only by a sum of two such functions, suggesting the presence of at least two subpopulations of events with different modal amplitudes. According to our estimates, two-thirds of the mEPSCs in FSIs belong to the high-amplitude subpopulation, and the modal amplitude in this subpopulation is approximately two times larger than that in the low-amplitude subpopulation. Using different statistical models, varying binning size, and data subsets, we confirmed the robustness and consistency of these findings.